Spatial variation of water holding capacity as an evidence for the needs of precision irrigation - Norizan, Mohd Shahkhirat; Wayayok, Aimrun; Abdullah, Ahmad Fikri; Mahadi, Muhammad Razif; Abd Karim, Yahya (MDPI AG, 2021)
Malaysia receives a lot of water from its two main monsoon periods. Generally, there is a lot of precipitation throughout the year, with drought periods lasting less than three months. To date, irrigation has been treated homogenously, even though soil properties can vary spatially over a field, requiring site-specific applications. The aim of this study was to establish an irrigation management zone (IMZ) covering 23.4 ha, which was previously determined under the same soil series. Soil sampling was done according to a grid system over an area of 100 m × 100 m. Three soil depth ranges were examined for every sampling point, namely 0–30, 30–60, and 60–90 cm from the soil surface. Samples were taken to a laboratory for physical analysis and determination of the available water-holding capacity (AWHC). Delineation of AWHC values was achieved using GIS software and the Kriging method. Estimated irrigation depth (EID) data for the plantation were collected for the years 2016 and 2017. Afterward, EID and total net irrigation (TNI) data were simulated in the FAO Cropwat model and compared. The results showed that clay, sand, and organic matter (OM) distributions varied with soil depth; however, no strong correlation was found between these variable with AWHC. The IMZ was classified into three areas named zones A, B, and C, ranging from 79 to 167 mm. The crop water requirement (CWR) was 667 mm in 2016 but only 260 mm in 2017. Based on the AWHC values, the EID for 2016 was found to be below the TNI requirement range of about 106 to 110 mm. In contrast, the EID range was approximately 34 to 62 mm and above TNI requirements for 2017. This study indicates that water inputs for irrigation can be optimized with knowledge of the water-holding capacity of a specific soil. Subsequently, this can be related to crop yield and the impact on sustainable agriculture.